IDENTIFICATION OF CITRUS WHITEFLY, HOST OF ENTOMOPATHOGENIC FUNGI (ASCHERSONIA PLACENTA) IN BALI INDONESIA - Merthaningsih, Ni Putu; Sudiarta, I Putu; Wirya, Gusti Ngurah Alit Susanta (International Journal of Biosciences and Biotechnology; Vol 7 No 2 (2020), 2020)
One of the pests of citrus is whitefly that, causes damage directly or/and indirectly to the citrus production. To control whitefly the farmer usually use chemical insecticide, however the utilization of chemical insecticide has been reported to haves many negative effect. To minimize the utilization of chemical insecticide, the environmentally friendly method is needed. One of the method is to utilize the natural enemies. Natural enemies are including, parasitiod, predator as well as insect pathogen (entomopathogen). In 2017 entomopathogenic fungi Aschersonia placenta was found to be associated with citrus whitefly in Bali Indonesia. However the species of whitefly has not been identified. In this research the identification of whitefly, the host insect of A. placenta was conducted based on morphological and molecular identification. Morphological identification of whitefly use puparial stage, started with sample preparation by Slide Mounting Protocol. The target  of mitochondrial cytochrome c oxidase subunit I (mtCOI) gen was successfully amplified (700 bp) by PCR using forward primer LCO 5'GGTCAACAAATCATAAAGATATTGG3' and reverse primer HCO 5'TAAACTTCAGGGTGACCAAAAAATCA3'. The phylogenetic analysis using software ChromasPRO, Molecular Evolutionary Genetics Analysis (MEGA 5.05), PAUP, BioEdit, and TreeGraph2 was conducted. The result shows that the mtCOI sequence of P. minei from Bali (LC491421) has the highest percentage among others with MK421974 P. minei (score homology 96%). The morphological recognition and sequence analysis show that the species of citrus whitefly is  Paraleyrodes minei .